Proposed Business Strategy to Increase the Number of Customers for a Conveyor Belt Company - Winsya Hesaputri Suryawan; Budi Rahardjo (AIBPM Publisher, 2021)
PT. XYZ is a company that provides conveyor belt needs for its clients with an office location in Central Java. PT. XYZ is currently getting a profit that is deemed not high enough for its shareholders even though it has established business relationships with leading companies. Some of the causes that make the low profit are the lack of a number of clients to work with, the limited company resources, and the high cost of packaging goods. This research will focus on the problem of the lack of a number of PT. XYZ's customers. Using the Five (5) Whys method, it was found the root cause analysis of the PT. XYZ is because of the number of industrial areas surrounding company is currently not much. Solutions that can be done in overcoming these problems are to apply market strategies such as market expansion, market development, diversification, or product development. In solving these problems, the SWOT Analysis method and research studies of previous studies are used. The results showed that market expansion was the chosen solution. This research approach can be used by companies that have similar problems.